2019
DOI: 10.1093/ehjcr/ytz091
|View full text |Cite
|
Sign up to set email alerts
|

Successful catheter ablation of premature ventricular contractions triggering torsade de pointes in a small infant with histiocytoid cardiomyopathy: a case report

Abstract: Background A short-coupled variant of torsade de pointes (ScTdP) is rare and resistant to medical treatment. There has not been a reported catheter ablation (CA) of a short-coupled premature ventricular contraction (PVC) triggering ScTdP in an infant. Case summary A neonate was referred to our hospital on the day of birth for Wolff–Parkinson–White syndrome, repeated episodes of supraventricular tachycardia, and a left ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 3 , 4 Generally, arrhythmia control in histiocytoid cardiomyopathy is challenging with no specific therapy. 5 , 6 To our knowledge, this is the first case report of histiocytoid cardiomyopathy with refractory ventricular arrhythmias controlled by oral medication.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“… 3 , 4 Generally, arrhythmia control in histiocytoid cardiomyopathy is challenging with no specific therapy. 5 , 6 To our knowledge, this is the first case report of histiocytoid cardiomyopathy with refractory ventricular arrhythmias controlled by oral medication.…”
Section: Discussionmentioning
confidence: 85%
“… 3 There is no specific treatment for arrhythmias of histiocytoid cardiomyopathy. Cataldo et al 5 and Hirano et al 6 reported the cases of histiocytoid cardiomyopathy treated with radiofrequency ablation but their outcomes were not satisfactory.…”
Section: Introductionmentioning
confidence: 99%